The impact of education on household income in rural Vietnam - Hung Van Vu (International Journal of Financial Studies, 2020)
Using data from the 2018 Vietnam Household Living Standard Survey, our study investigates the impact of education on household income in rural Vietnam. Both mean and quantile regression analyses were employed to analyze the impact of education. We found that education has a positive effect on the household income after controlling for various factors in the models. However, quantile regression analysis reveals that the effect of schooling years increases with quantiles, suggesting that education bring higher returns for richer households. We also found that households with the heads having higher qualifications or vocational education tend to earn higher income levels. Combined together, these findings imply that while education was found to increase household income, it increases income inequality in rural Vietnam. Our research findings suggest that improving the access of poor households to better education is expected to increase their income and reduce inequality in rural Vietnam.
Keywords: I21; I24; I25; I26; 330; education; household income; inequality; quantile regression; rural Vietnam